Development of a prolonged-release gastroretentive tablet formulation of ciprofloxacin hydrochloride: Pharmacokinetic characterization in healthy human volunteers - Mostafavi, Abolfazl; Emami, Jaber; Varshosaz, Jaleh; Davies, Neal M.; Rezazadeh, Mahboubeh (International journal of pharmaceutics, 2011)
Controlled-release floating tablets (●), conventional immediate release tablets (○), and co-administration of conventional immediate release and controlled release floating tablets (▴) in healthy volunteers. The fluroquinolone anti-biotic ciprofloxacin is primarily dissolved and absorbed from the upper part of the GI tract. We, therefore, aimed to develop a prolonged release gastroretentive (GT) formulation of ciprofloxacin that could be administered once daily with a conventional tablet (CT). A variety of polymers and effervescent properties were utilized to optimize the desired disposition profile. Tablets were prepared by the direct compression technique and evaluated for physical properties, swelling, floating, and drug release. In vivo studies were also carried out on the optimized GT formulation and CT in healthy volunteers. A very sensitive and reliable HPLC method was developed to measure plasma concentration of ciprofloxacin. The duration of floating times were predominantly >24 h and floating lag times <20 s. The drug release mechanism followed zero order kinetics. C max, T max, and AUC 0–∞ of GT vs CT were 0.945 ± 0.29 vs 2.1 ± 0.46 μg/ml, 6.0 ± 1.42 vs 1.42 ± 0.59 h and 8.54 ± 1.87 vs 9.45 ± 2.12 μg/ml/h, respectively. Pharmacokinetic parameters indicate that the developed GT formulation extended the pharmacokinetic profile achieved with CT. The C max/MIC and AUC 0–∞/MIC, which are indicative of eradication of pathogens, following co-administration of GT with CT were comparable to those of twice-daily administration of CT alone.